In order to solve this problem, we must solve an equation.
First, we need to define our unknown.
Let's call our number "n".
So, the sum of the number and 6 is the same as saying n+6
Then we need to multiply it by 2 (since it's twice the sum)
2(n+6)
This whole thing is equal to three times of the difference of the number and 8
n-8 is equal to the difference between the number and 8, then we need to multiply it by three.
3(n-8)
now, we set both sides equal and solve
![2(n+6)=3(n-8)\\2n+12=3(n-8)\\2n+12=3n-24\\12=n-24\\36=n](https://tex.z-dn.net/?f=2%28n%2B6%29%3D3%28n-8%29%5C%5C2n%2B12%3D3%28n-8%29%5C%5C2n%2B12%3D3n-24%5C%5C12%3Dn-24%5C%5C36%3Dn)
The number is 36